Plant-insect interactions across the Triassic–Jurassic boundary in the Sichuan Basin, South China - Xu, Yuanyuan; Wang, Yongdong; Li, Liqin; Lu, Ning; Zhu, Yanbin; Huang, Zhuanli; McLoughlin, Stephen (Frontiers in Ecology and Evolution, 2024)
Plants and insects are the most diverse and ecologically important organisms in the terrestrial biosphere. Their interactions are also among the richest biotic relationships, and offer significant insights into the evolution of terrestrial ecosystem complexity through the geological record. This investigation of the late Rhaetian Xujiahe and the earliest Jurassic Zhenzhuchong floral assemblages provides the first data on foliar herbivory generated by terrestrial arthropods across the Triassic-Jurassic transition in the eastern Tethys (East Asia) region. The damage types from two fossil assemblages are collectively attributed to seven functional feeding and egg-laying categories (i.e., hole feeding, margin feeding, surface feeding, skeletonization, piercing and sucking, oviposition, and galling).Most feeding strategies are spread across the major plant groups and persist through the Triassic-Jurassic boundary, with the exception of skeletonization (a category of external foliage feeding), which was restricted to the latest Triassic within dipteridacean ferns. The survey reveals that the respective frequency and diversity of interactions between plants and insects prior to and following the end-Triassic mass extinction event are almost the same, despite a substantial turnover of floral components. This suggest that insect herbivores were largely able to transfer to alternative (but commonly related) plant groups during the dramatic floristic turnover and environmental changes at the end of the Triassic.Pterophyllum and prominent ridges on the rachises of some ferns and bennettites are interpreted as adaptations for defense against insect herbivores. A few differences in taxonomic composition and herbivory representation between the latest Triassic Xujiahe flora and the earliest Jurassic Zhenzhuchong flora are more likely to be related to collection and preservational biases rather than reflecting palaeoecological changes. We encourage further investigations exploring the distribution of insect damage in fossil floras from other palaeolatitudinal zones and spanning other major extinction events to develop a better understanding of terrestrial ecosystems responses to major crises in Earth's history.